Integrating altimetry derived gravity anomalies with ship-borne gravity data for Africa - ABD-ELMOTAAL, Hussein; MAKHLOOF, Atef (Contributions to Geophysics and Geodesy, 2023)
The most comprehensive and precise gravity data for the sea region must be obtained for the Sub-Commission of gravity and geoid for Africa (The African Gravity and Geoid sub-commission (AGG) belongs to the Commission 2 of the International Association of Geodesy (IAG)). There are two gravity data sets available for the marine region. The first is the ship-borne gravity data set, which has large gaps but has good precision. The second is the regularly covered and less accurate gravity anomalies generated from satellite altimetry. The most effective fusion of the previous two gravity data sets is examined in this research. First, each data set has passed a gross-error detection scheme. Points with differences of more than 4.5 mGal between estimated and observed gravity anomalies were eliminated because they were deemed to have a blunder. The base has been entirely taken from the ship-borne gravity points since they are more precise (after the gross-error removal). At the altimetry data points, assessments have been made of the discrepancies between gravity anomalies generated by altimetry and ship-borne gravity anomalies. In most places, the employed ship-borne data and the used altimetry data exhibit an acceptable level of consistency. If altimetry-derived gravity anomalies deviate by more than 20 mGal from ship-borne gravity anomalies, they are disregarded. For the majority of nations, especially those with oceanic and maritime borders like Egypt, a mix of land gravity data and shipborne and altimetry data is necessary for exact regional geoid modelling. In nations where there are significant gaps in the terrestrial gravity anomalies, the shipborne and altimetry free-air anomalies are significant. Moreover, the smoothness of gravity database resulting from this investigation is used significantly in geophysical interpretation.